2014
DOI: 10.1377/hlthaff.2013.1179
|View full text |Cite
|
Sign up to set email alerts
|

Hospital And ED Use Among Medicare Beneficiaries With Dementia Varies By Setting And Proximity To Death

Abstract: Hospitalizations and emergency department (ED) visits for people with Alzheimer's disease and related disorders are of particular concern because many of these patients are physically and mentally frail, and the care delivered in these settings is costly. Using data from the Health and Retirement Study linked with Medicare claims from the period 2000-08, we found that among community-dwelling elderly fee-for-service Medicare beneficiaries, those who had dementia were significantly more likely than those who di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
164
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(177 citation statements)
references
References 25 publications
5
164
2
3
Order By: Relevance
“…Based on reasons for admission recorded in billing data (i.e., principal discharge diagnosis codes), it is increasingly suggested that persons with dementia are over-hospitalized, and many hospitalizations are potentially preventable. [20,21,65,69,71-73,79]. Our findings do not appear to suggest excessive use of surgery in dementia patients—there is a possibility that surgery is underutilized.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Based on reasons for admission recorded in billing data (i.e., principal discharge diagnosis codes), it is increasingly suggested that persons with dementia are over-hospitalized, and many hospitalizations are potentially preventable. [20,21,65,69,71-73,79]. Our findings do not appear to suggest excessive use of surgery in dementia patients—there is a possibility that surgery is underutilized.…”
Section: Discussionmentioning
confidence: 52%
“…[65-68] Regarding comparisons between prevalent dementia and CN, our results reflect pooled conclusions by others that a) medical costs are higher for individuals with dementia compared to those without dementia; b) differences are especially great for hospital inpatient costs; c) among hospitalized patients, those with dementia are admitted for different reasons and longer stays; d) dementia subjects with selected comorbid conditions have higher costs than those for subjects with similar conditions but no dementia; and e) dementia-associated use is reduced following adjustment for comorbidity. [3,5,19,20,23,69-73]…”
Section: Discussionmentioning
confidence: 99%
“…Older adults with dementia are at increased risk of hospital admission for reasons that are not clear (13). Potential contributing factors that have been largely unaddressed are the behavioral and psychological symptoms of dementia (BPSD [also referred to as neuropsychiatric symptoms]) and associated caregiver distress.…”
Section: Objectivementioning
confidence: 99%
“…Previous analyses have found an association between BPSD and medical costs, although BPSD were simply categorized as “high” (13) or “present” (14) in those studies, and the role of caregiver distress was not considered. In addition, costs were estimated from a caregiver survey and emergency department (ED) utilization was not considered, although ED use is known to be elevated in patients with dementia (3). A recent prospective Scottish cohort study found high overall BPSD to be associated with hospital admission, although overall caregiver distress was not significant; ED utilization was not considered (15).…”
Section: Objectivementioning
confidence: 99%
“…The Census found that from 2000 to 2010, the number and proportion of elderly living in facilities declined while the overall population of elderly grew. Feng et al found comparable rates of emergency department use in community dwelling elderly and nursing home residents with dementia from 2000 to 2008; however they did not separately analyze people living in assisted living or other community plus services settings (14). Caffrey (8) reported similar rates of Medicaid use among people living in community plus services settings.…”
Section: Discussionmentioning
confidence: 99%